METACOGNITIVE STRATEGIES OF TEACHING ENGLISH SPEAKING SKILLS TO NON-ENGLISH ADULT LEARNERS - Ali Amran (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2013)
ABSTRACTAs we probably know that there so many teaching strategies applied by thoseEnglish teachers But in reality there still many leaners ( adults ) ﬁnd thatthe are good enough some are very good, but some are not very interestingthat make adult learners feel bored in mastering this universal Englishga. Be all agree that all foreign teaching strategies are relevant to those foreign But there is no guarantee that those foreign ones can help local adultlearners enjoy learning in order to master the knowledge of Eniglish.her hasbeen conducting these metacognitive of teaching English speakingquite many years. He ﬁnds that there are some positive advantages that adult can obtain and apply them in learning English. Adult learners in this case is who graduate from high school levels and they are not majoring in English.